2018
DOI: 10.1002/cncr.31316
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic testing for hereditary prostate cancer: Current status and limitations

Abstract: A significant proportion of prostate cancer diagnoses may be associated with a strong hereditary component. Men who have multiple single-gene polymorphisms and a family history of prostate cancer have a significantly greater risk of developing prostate cancer. Numerous single-gene alterations have been confirmed to increase the risk of prostate cancer. These include breast cancer genes 1 and 2 (BRCA1 and BRCA2, respectively), mutL homolog 1 (MLH1), mutS homologs 2 and 6 (MSH2 and MSH6, respectively), postmeiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
92
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 62 publications
(157 reference statements)
0
92
1
Order By: Relevance
“…Additionally, associations between germline variations and familial prostate cancer have been reported . Recently, genetic variants in tumor‐suppressor gene HOXB13 and DNA‐repair genes, such as BRCA1/2 , MLH1 , MSH2/6 , CHEK2 and ATM , were found to be involved in the risk of morbidity of prostate cancer . Additionally, various germline polymorphisms, such as single‐nucleotide polymorphism, have been shown to be weakly associated with the risk of prostate cancer .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, associations between germline variations and familial prostate cancer have been reported . Recently, genetic variants in tumor‐suppressor gene HOXB13 and DNA‐repair genes, such as BRCA1/2 , MLH1 , MSH2/6 , CHEK2 and ATM , were found to be involved in the risk of morbidity of prostate cancer . Additionally, various germline polymorphisms, such as single‐nucleotide polymorphism, have been shown to be weakly associated with the risk of prostate cancer .…”
Section: Discussionmentioning
confidence: 99%
“…21 Recently, genetic variants in tumor-suppressor gene HOXB13 and DNA-repair genes, such as BRCA1/2, MLH1, MSH2/6, CHEK2 and ATM, were found to be involved in the risk of morbidity of prostate cancer. 22 Additionally, various germline polymorphisms, such as single-nucleotide polymorphism, have been shown to be weakly associated with the risk of prostate cancer. 8 Intriguingly, germline mutations in DNA repair genes are suggested to be associated with both progression of prostate cancer 7 and worse prognosis with hormone therapy, 10 possibly partially accounting for the slightly better prognoses with hormone therapy in low-or intermediate-risk patients; fewer patients with family history and low-or intermediate-risk might carry deficiencies in DNA repair genes than those at high risk.…”
Section: Discussionmentioning
confidence: 99%
“…127 Prostate cancer is extremely heterogeneous compared to other tumours, and accordingly, various familial and sporadic mutations have been identified that increase its risk. 128,129 Those with multiple single-gene polymorphisms and a family history of prostate cancer are at the highest risk. 126,[128][129][130][131][132] These include BRCA1 and BRCA2, MMR mutations including MLH1, MSH2 and MSH6, PMS2, HOXB13, checkpoint kinase 2 CHEK2, NBN, BRCA1-interacting protein C-terminal helicase 1 (BRIP1), and ATM.…”
Section: Prostate Cancermentioning
confidence: 99%
“…128,129 Those with multiple single-gene polymorphisms and a family history of prostate cancer are at the highest risk. 126,[128][129][130][131][132] These include BRCA1 and BRCA2, MMR mutations including MLH1, MSH2 and MSH6, PMS2, HOXB13, checkpoint kinase 2 CHEK2, NBN, BRCA1-interacting protein C-terminal helicase 1 (BRIP1), and ATM. [129][130][131] The potential of these findings is underscored by the recent approval of olaparib for BRCA1/BRCA2 or ATM-mutated, metastatic, castrate-resistant prostate cancer.…”
Section: Prostate Cancermentioning
confidence: 99%
“…As the subject of quite a few studies, compared to other common tumor, the development or morbid condition of prostate cancer and further study is needed. Including old aging, ethnicity, individual heredity factors and family history [2,4] both were the generally-accepted risk factors of prostate cancer. Thus, diagnosing the individuals in danger of hereditary prostate cancer and potential other factors which contribute to the early detection and handle the development of PCa was urgent for us [5].…”
Section: Introductionmentioning
confidence: 99%